The OBTAINS study: A nationwide cross-sectional survey on the implementation of extended or continuous infusion of β-lactams and vancomycin among neonatal sepsis patients in China - Zhou, Pengxiang; Cheng, Yinchu; Cao, Guangna; Xing, Yan; Zhai, Suodi; Tong, Xiaomei; Yang, Kehu (Frontiers in Pharmacology, 2022)
Background: Dosing strategies of β-lactams and vancomycin should be optimized according to pharmacokinetic/pharmacodynamic principles. However, there is no available data indicating the implementation of extended infusion (EI) or continuous infusion (CI) administration in the management of neonatal sepsis. Methods: A nationwide cross-sectional survey was conducted and the pediatricians from 31 provinces in China were enrolled. A multidisciplinary team created the questionnaire, which had three sections and a total of 21 questions with open- and closed-ended responses. The survey was then conducted using an internet platform in an anonymous way. The data was eventually gathered, compiled, and examined. To identify the risk factors associated with the implementation of EI/CI, logistic regression was carried out. Results: A total of 1501 respondents answered the questionnaires. The implementation of EI/CI of β-lactams and vancomycin were only available to one-third of the respondents, and the prolonged strategy was primarily supported by guidelines (71.25%) and advice from medical specialists (55.18%). A significant fraction (72.94% to 94.71%) lacked a strong understanding of the infusions' stability. Additionally, it was discovered that more frequent MDT discussions about antibiotic use and the appropriate time pediatricians worked in the neonatal ward were associated with an increase in the use of the EI/CI strategy. Conclusions: The EI/CI strategy in neonatal sepsis was not well recognized in China, and it is necessary to establish a solid MDT team with regularly collaborates. In the near future, guidelines regarding prolonged infusion management in neonatal sepsis should be developed.